Wideband dual segment rectangular dielectric resonator antenna terminate in bio-media - Gangwar R.K.; Singh S.P.; Kumar D. (My University, 2025)
In this paper a wideband dual segment rectangular dielectric resonator antenna (RDRA) designed for WiMAX band (3.2 GHz and 5.5 GHz) and power absorption in a homogenous biomedium (muscle layer) in proximity with the proposed antenna are described. The simulation results for the characteristics of the proposed antenna and the specific absorption rate (SAR) distribution in the muscle layer are discussed.